As funções exponencial e logarítmica: uma abordagem para o professor do ensino básico - Alves, Cícero dos Santos (2014)
In this work we make an elementary approach to the exponential function in order to understand the meaning of powers with natural exponent, integer, rational and irrational as well as the properties that make it one of the most important functions of mathematics. In parallel, another approach will be showing these properties using a powerful tool of mathematics: differential and integral calculus. We will also discuss the logarithmic function because it is the inverse of the exponential function and being as important as this.